Closer - Tan, Vivien Shi Hui (2016)
Closer is an immersive multidisciplinary light installation that invites viewers to contemplate about love and loss. The installation is separated into three portions — a larger-than-life lantern sculpture, a video installation of cinemagraphs, and a book further explaining the work.